Genome-wide identification and characterization of ALKB homolog gene family in wheat (Triticum aestivum L.) - Wang, Pengkun; Zhang, Tianye; Wu, Zechi; Yu, Lei; Liao, Pingan; Yang, Jian; Sun, Bingjian (Frontiers in Plant Science, 2025)
IntroductionN6-methyladenosine (m6A) is the most prevalent posttranscriptional modification in eukaryotic mRNAs. AlkB homologs (ALKBHs) are involved in plant responses to stress by modulating m6A methylation. However, homologous genes in wheat remain largely uncharacterized.Methods and resultsIn this study, 30 ALKBH genes were identified in wheat, and analyzed their physicochemical properties. The phylogenetic analysis allowed the classification of these genes into seven distinct subfamilies. Additionally, their conserved domains, motif compositions, gene structures, chromosomal localization, and synteny, and the predicted cis-acting elements within their promoters were examined. Expression analysis revealed that TaALKBH9B-5 exhibited the highest expression and its demethylase activity was investigated. Furthermore, TaALKBH9B-5 was significantly upregulated in response to abscisic acid treatment and cold stress, indicating a positive regulatory trend.DiscussionIn conclusion, this study provides a comprehensive genomic assessment of the TaALKBH gene family and offers a theoretical framework for understanding the role of TaALKBH9B in the response to abiotic stress in wheat.